PERHITUNGAN RISIKO KREDIT KPR PADA BANK XYZ MENGGUNAKAN METODE CREDITRISK+ - AFIFAH, SORAYA SARAH; DHARMAWAN, KOMANG; SRINADI, I GUSTI AYU MADE (E-Jurnal Matematika; Vol 11 No 2 (2022), 2022)
Credit risk is a risk that is often encountered by banks in lending, especially mortgages . Banks can get losses if the risk is not anticipated properly . The purpose of this study is to estimate the number of losses (expected loss and unexpected loss) obtained by Bank XYZ due to default debtors and to estimate the amount of economic capital that must be provided by Bank XYZ in anticipating unexpected losses. The study was conducted using the CreditRisk+ method with a Poisson distribution approach. The ratio between expected loss and unexpected loss obtained from the calculation results is 57%. With the value of economic capital that needs to be provided by Bank XYZ is Rp . 647 . 594 . 176 . 768 ,-. This means that Bank XYZ needs to monitor the outstanding credit of their debtors who experience default in the credit portfolio in order to avoid possible losses and provide economic capital to cover these losses. So that the estimated value of economic capital can be used as a capital benchmark to anticipate maximum losses and as an indicator for Bank XYZ to earn income from credit activities .